Child Labor and Development : An Introduction - Basu, Kaushik; Tzannatos, Zafiris (Washington, DC: World Bank, 2014)
Long neglected by economists, child labor has experienced a sudden resurgence of interest as a subject of research and analysis since the mid-1990s. This is surprising at first glance, because the global incidence of child labor has been on the decline for several decades now. What accounts for the increased interest? One factor is the growing emphasis in the development literature on poverty reduction, particularly among the most vulnerable sections of the population, which includes children, especially working children. Simultaneously, with the heightened recognition of the importance of human capital accumulation as a catalyst and perhaps even a prerequisite for development, child labor is viewed as a major impediment to economic progress.